Optimization of decolorization of methylene blue by lignin peroxidase enzyme produced from sewage sludge with Phanerocheate chrysosporium - Alam, Md. Zahangir; Mansor, Mariatul F.; Khan Chowdhury, Ahmed Jalal (Elsevier Science, 2009)
Optimization of decolorization of methylene blue (MB) dye by lignin peroxidase (LiP) enzyme produced by white-rot fungus Phanerochaete chrysosporium using sewage treatment plant (STP) sludge as a major substratewas carried out in the laboratory.Optimization by the one-factor-at-a-time (OFAT) and statistical approachwas carried out to determine the process conditions on optimum decolorization ofMBdye using LiP enzyme in static mode. The OFAT method indicated that the optimum conditions for decolorization of MBdye (removal: 14–40%)was at temperature 55 ◦C, pH 5.0 with hydrogen peroxide (H2O2) concentration 4.0mM, MB dye concentration 20 mg/L and LiP activity 0.487 U/ml. The addition of veratryl alcohol to the reaction mixtures did not contribute any further increases in decolorization. The initial concentration of MB and the activity of LiP enzyme were further optimized using response surface methodology (RSM).The contour and surface plots suggested that the optimum initial concentration of MB and LiP activity predicted were 15 mg/L and 0.687 U/ml, respectively for the removal of 65%. The validation of the model showed that the decolorization process gave the higher removal of 90% in agitation mode compared to the static mode with 65% for 60 min of incubation time by LiP enzyme.